Corrosion in modular revision hip stem tapers: a retrieval analysis - Bormann, Therese; Yan, Haolan; Jäger, Sebastian; Schonhoff, Mareike; Kretzer, Jan Philippe (Journal of orthopaedic research, 2025)
In revision hip arthroplasty, modular stems enable intraoperative adjustment of the biomechanics of the hip to ensure a stable joint function even in complex anatomical cases. Modular stem junctions, however, carry the risk of junction degradation due to corrosive processes or even junction breakage. Fretting-corrosion has been mentioned as precursor of junction breakage but has hardly been systematically assessed. To investigate relations between corrosion and fretting, and implant and patient specific parameters and connection strength, respectively, a collection of 53 retrieved modular hip stems of different implant systems was investigated. Corrosion and fretting at the stem-neck taper connection were rated with a modified Goldberg score. Taper contamination was assessed with a similar scoring system. If the hip stems were still joint to the neck piece, the push-out force to detach the parts was recorded as a measure for taper junction strength. A multivariate regression analysis revealed that corrosion and fretting were significantly affected by implantation time, taper contamination, body weight and implant system. Taper junction strength was not altered by corrosion or fretting but by taper contamination. The results indicate that implant geometry parameters are not related to the extent of corrosive degradation at the junction, but taper contamination significantly increased corrosion at taper surfaces. This underlines the importance of the cleanliness of the taper surfaces during hip stem assembly for a long-term stability of the modular implant.
Gesehen am 15.01.2026